Cultural policies and communication policies - Cornejo-Polar, Jorge (1989)
It should be noted on the other hand that the concept of cultural policies has not remained unchanged from its appearance until today. On the contrary, it is possible to detect an interesting and sustained process of complexity and improvement that has even given rise to talk of successive generations of cultural policies or emphasis on the different ways in which it has been understood or understood and the term in question applies. What must be clearly established beforehand is that at present a fundamental instrument for the task of governing any State is cultural policy.